Sustained immunological memory to SARS-CoV-2 antigens. Three years of observation - Afridonova, Z. E.; Toptygina, A. P.; Semikina, E. L. (Infekt͡s︡ii͡a︡ i immunitet, 2024)
The COVID-19 pandemic has ended, but SARS-CoV-2 continues to actively circulate and mutate in the human population. In this regard, it is important to understand for how long post-infectious and post-vaccination immunity may last and how effectively established immunity could act against new mutant SARS-CoV-2 strains. The aim was to study humoral and cellular immunity in a group of COVID-19 convalescent subjects within 3 years after the primary infection. The longitudinal study included 38 adults aged 23–72 years with PCR-confirmed mild or moderate COVID-19 in the second half of 2020. Within three-year follow-up after the onset, the subjects were examined every 6 months for the level of humoral and cellular immunity against SARS-CoV-2 antigens. The parameters of humoral immunity were assessed by enzyme immunoassay using “SARS-CoV-2-IgG quantitative-ELISA-BEST” kits (Vector-Best JSC, Novosibirsk, Russian Federation) for S-protein and “N-CoV-2-IgG PS” (Saint-Petersburg Pasteur Institute, St. Petersburg, Russian Federation) specific to the N-protein. Cellular anti-SARS-CoV-2 immunity was analyzed by evaluating surface CD107a expression on CD8high lymphocytes stimulated with the SARS-CoV-2 S- or N-antigens. It was shown that the dynamics of antibody levels against SARS-COV-2 antigens depends on antigen (S- or N-protein) type, antibody class (IgG or IgA) as well as individual contact history with new SARS-CoV-2 strains. The dynamics of cytotoxic CD8highCD107a+ lymphocyte percentage is moderately positively correlated with that of the corresponding anti-S or N antibody levels. At the same time, change in the levels of both humoral and T-cell responses to SARS-CoV-2 S- or N-protein antigens are weakly negatively correlated with each other. A strong positive correlation was found between changes in the anti-S IgG antibody level and avidity. Avoiding the anti-S IgG neutralization due to frequent mutations of new SARS-CoV-2 strains leads to induced new primary immune responses against SARS-CoV-2 antigens along with the activation of existing responses formed to previous coronavirus strains. The study of immune responses against SARS-CoV-2 antigens allows to predict the persistence of high SARS-CoV-2 anti-S antibody and T-cell response levels.